2018
DOI: 10.3904/kjim.2016.223
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary intake and postlaparoscopic cholecystectomic symptoms in patients with gallbladder disease

Abstract: Background/AimsAfter cholecystectomy, patients have reported postcholecystectomic syndromes such as abdominal symptoms, dyspepsia, and diarrhea, which suggest a relationship between cholecystectomic symptoms and diet, although the details of this association remain unclear. The present study investigated the hypothesis that dietary intake of nutrients and foods was significantly associated with postcholecystectomic syndromes.MethodsGallstone patients (n = 59) who underwent laparoscopic cholecystectomy were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…The same conclusion was obtained by [1] who concluded that a low-fat diet does not seem to have an influence on the improvement of symptoms after cholecystectomy [1]. In [4] other results were obtained which concluded that postchol-ecystectomy symptoms were positively associated with intake of cholesterol and negatively associated with intake of vegetables suggesting that diet was plays a role in postcholecystemic symptoms. Patients with gallstones are often affected by alimentary disorders contributing to the onset of gallstones disease.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The same conclusion was obtained by [1] who concluded that a low-fat diet does not seem to have an influence on the improvement of symptoms after cholecystectomy [1]. In [4] other results were obtained which concluded that postchol-ecystectomy symptoms were positively associated with intake of cholesterol and negatively associated with intake of vegetables suggesting that diet was plays a role in postcholecystemic symptoms. Patients with gallstones are often affected by alimentary disorders contributing to the onset of gallstones disease.…”
Section: Discussionsupporting
confidence: 72%
“…In our study there was one patient presented with diarrhea. In normal diet group there was one patient (5%) patient presented with diarrhea and in fat restriction group there was zero patient presented with diarrhea as shown in Figure (4). In our study there was one patient presented with steatorrhea.…”
Section: Follow Up After Dischargesupporting
confidence: 42%
See 1 more Smart Citation
“…Fifteen studies reported various other etiologies for incident long-term abdominal symptoms after LC. Changed dietary intake, mainly waiving preoperative dietary restrictions, or physical inactivity may attribute to symptoms after LC [61, 75].…”
Section: Incident Symptomsmentioning
confidence: 99%
“…Notably, PCS patients were also more likely to consume bread than rice for breakfast. Dietary habits were analysed by a food frequency questionnaire postcholecystectomy and at 3 months [38].…”
Section: Effectiveness Of Post-cholecystectomy Dietary Modifications and Relation To Gut Microbiomementioning
confidence: 99%